2007
DOI: 10.1001/archinte.167.7.684
|View full text |Cite
|
Sign up to set email alerts
|

Older Age and the Response to and Tolerability of Antiretroviral Therapy

Abstract: Background: The unique health needs of a growing older adult population infected with human immunodeficiency virus (HIV) require study, especially in terms of the response to and tolerability of highly active antiretroviral therapy (HAART). Methods: Changes in HIV clinical markers after HAART initiation were compared among 2259 patients aged 18 to 39 years (reference group), 1834 patients aged 40 to 49 years, and 997 patients 50 years or older enrolled in an integrated health care system. Results: Patients 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
123
4
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 36 publications
(15 reference statements)
21
123
4
3
Order By: Relevance
“…In our study, however, the incidence of toxic events in the sample years was surprisingly similar, differing from those of previous studies [35,39] and in line with another recent report [19]. This may be partly related to the epidemiological trends and clinical differences evidenced in the 2 sample populations, as the higher proportion of younger and less advanced patients in 1998 may have possibly counterbalanced the higher toxicity of first generation drugs used in that year [40,41]. Interestingly, the incidence of changes in the initial HAART regimen due to drug toxicity was similar in 1998 and in 2006.…”
Section: Or (95% CIcontrasting
confidence: 56%
“…In our study, however, the incidence of toxic events in the sample years was surprisingly similar, differing from those of previous studies [35,39] and in line with another recent report [19]. This may be partly related to the epidemiological trends and clinical differences evidenced in the 2 sample populations, as the higher proportion of younger and less advanced patients in 1998 may have possibly counterbalanced the higher toxicity of first generation drugs used in that year [40,41]. Interestingly, the incidence of changes in the initial HAART regimen due to drug toxicity was similar in 1998 and in 2006.…”
Section: Or (95% CIcontrasting
confidence: 56%
“…[71][72][73][74][75][76][77] Interestingly, this finding is not explained by differences in virological response, as older HIV-infected patients tend to have a superior virological outcome when compared with younger patients. [78][79][80][81][82][83] Some suggests that these finding may be linked with higher adherence in older patients, 78,[84][85] but other authors reported a higher risk of inadequate adherence in HIV patients who have other comorbidities and take other medications besides HAART. [86][87] While virological response seems not to be influenced by age, at least biologically, older patients have lower CD4C T-cell gain compared with younger persons, [88][89][90][91][92][93][94][95] even when adjusted for antiretroviral therapy regimens.…”
Section: Clinical Outcomementioning
confidence: 99%
“…Finally, the pharmacokinetics of prescribed drugs is also influenced by change in body composition which typically occurs in the elderly, such as increased in body fat and decrease in total body water. 125 Special attention should then be made to adjust the dosage of antiretrovirals given these physiologic modifications occurring with age, as several works demonstrated an increase in drugrelated adverse events in older patientsv 78,[126][127][128][129][130][131][132] What to start…”
Section: Impact Of Aging On Drug Toxicity In Hiv-infected Patientsmentioning
confidence: 99%
“…Por último, a nivel médico, se evita hacer preguntas dirigidas para conocer su riesgo para la infección por el VIH. Todas estas circunstancias favorecen la "pérdida de oportunidad" diagnóstica (6,7).…”
unclassified
“…Si bien el inicio precoz puede retrasar el deterioro inmunológico y mejorar su pronóstico, no iniciarlo en fases precoces minimiza los efectos adversos del tratamiento. No debemos olvidar que los pacientes mayores infectados por el VIH tienen una mayor presencia de comorbilidades (hipertensión arterial, EPOC, diabetes mellitus,...) (6,13,14,17,18) que los obliga al uso de otras terapias específicas no relacionadas con la infección por el VIH (AINEs, inhibidores de la bomba de protones,…) con el consiguiente riesgo de interacciones (18), algunas de ellas graves.…”
unclassified